Unique cultural values of Madura cattle : is crossbreeding a threat? - Widi, T.S. Mastuti (Cambridge, 2014)
In Indonesia, crossbreeding local cattle with European beef breeds is widely promoted to stimulate beef production. Crossbreeding is threatening local breeds which have often multiple functions, including cultural roles. This study analysed the cultural values of Madura cattle and the impact of crossbreeding on local traditions in Madura island. Bull racing (karapan) and cow conformation contests (sonok) are traditional cultural events. Since 2001, crossbreeding with Limousin is allowed. The local government promotes also a conformation contest for crossbred (madrasin) cattle. Quantitative and qualitative information was collected through participatory approaches involving farmers, government officials, community groups, key informants, and through observation of sonok, karapan and madrasin events. Four cattle types could be distinguished: karapan, sonok, madrasin and conventional Madura cattle. These cattle were found in three discrete areas. Madura cattle participating in cultural events were valued at prices that were 2-3.5 times higher than cattle not participating in cultural events. Crossbreeding will not directly influence the cultural events or the management practices of Madura cattle in the karapan and sonok areas, however, outside the karapan and sonok areas, crossbreds are rapidly replacing conventional Madura cattle. The Madura example shows that cultural values of livestock can be a main driver for maintaining relatively small populations of local breeds. Keywords: Madura; bull racing; cattle contests; conservation; cultural values